Molecular Mechanisms of Non-ionotropic NMDA Receptor Signaling in Dendritic Spine Shrinkage - Stein, Ivar S. (J Neurosci, 2020)
Structural plasticity of dendritic spines is a key component of the refinement of synaptic connections during learning. Recent studies highlight a novel role for the NMDA receptor (NMDAR), independent of ion flow, in driving spine shrinkage and LTD. Yet little is known about the molecular mechanisms that link conformational changes in the NMDAR to changes in spine size and synaptic strength. Here, using two-photon glutamate uncaging to induce plasticity at individual dendritic spines on hippocampal CA1 neurons from mice and rats of both sexes, we demonstrate that p38 MAPK is generally required downstream of non-ionotropic NMDAR signaling to drive both spine shrinkage and LTD. In a series of pharmacological and molecular genetic experiments, we identify key components of the non-ionotropic NMDAR signaling pathway driving dendritic spine shrinkage, including the interaction between NOS1AP (nitric oxide synthase 1 adaptor protein) and neuronal nitric oxide synthase (nNOS), nNOS enzymatic activity, activation of MK2 (MAPK-activated protein kinase 2) and cofilin, and signaling through CaMKII. Our results represent a large step forward in delineating the molecular mechanisms of non-ionotropic NMDAR signaling that can drive shrinkage and elimination of dendritic spines during synaptic plasticity. SIGNIFICANCE STATEMENT Signaling through the NMDA receptor (NMDAR) is vitally important for the synaptic plasticity that underlies learning. Recent studies highlight a novel role for the NMDAR, independent of ion flow, in driving synaptic weakening and dendritic spine shrinkage during synaptic plasticity. Here, we delineate several key components of the molecular pathway that links conformational signaling through the NMDAR to dendritic spine shrinkage during synaptic plasticity.